2020
DOI: 10.1186/s13011-020-00311-4
|View full text |Cite
|
Sign up to set email alerts
|

Large and non-specific somatic disease burdens among ageing, long-term opioid maintenance treatment patients

Abstract: Objectives To describe and explore somatic disease burdens of ageing long-term patients in opioid maintenance treatment (OMT), a unique population emerging in countries offering OMT as a long-term treatment. Methods We used data from the Norwegian Cohort of Patient in Opioid Maintenance Treatment and Other Drug Treatment Study (NorComt). 156 patients enrolled for at least three of the past five years provided data during structured interviews, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…This result is in common with studies reporting excess mortality, particularly for respiratory disease in individuals with OUD or SUD compared with the general population [29,30]. Although we lacked information on smoking habits, the reported prevalence of smoking among Norwegian OAT patients is 91% [44], similar to other OAT populations [45][46][47]. Spirometry and volumetric computerized tomography (CT) screening may be appropriate for long-term heavy smokers for early diagnosis of chronic obstructive pulmonary disease and lung cancer, while smoking harm reduction interventions such as the use of snus (smokeless tobacco) [48] or e-cigarettes might be relevant for some if smoking cessation is difficult or not wanted.…”
Section: Discussionsupporting
confidence: 71%
“…This result is in common with studies reporting excess mortality, particularly for respiratory disease in individuals with OUD or SUD compared with the general population [29,30]. Although we lacked information on smoking habits, the reported prevalence of smoking among Norwegian OAT patients is 91% [44], similar to other OAT populations [45][46][47]. Spirometry and volumetric computerized tomography (CT) screening may be appropriate for long-term heavy smokers for early diagnosis of chronic obstructive pulmonary disease and lung cancer, while smoking harm reduction interventions such as the use of snus (smokeless tobacco) [48] or e-cigarettes might be relevant for some if smoking cessation is difficult or not wanted.…”
Section: Discussionsupporting
confidence: 71%
“…People with substance use disorders (SUD) in general, and opioid use disorder (OUD) in particular, are at risk of a range of adverse health effects. These negative effects include increased drug related and non-drug related mortality [ 1 , 2 ]; physical morbidity such as hepatitis C, chronic obstructive pulmonary disease and self-reported somatic symptoms [ 3 , 4 ]; and under-utilization of healthcare [ 3 , 5 , 6 ]. In addition, people with SUD also face stigma and discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…al. [ 20 ] showed that 81% of long-term OST patients reported that they had utilized PHC during the past six months, and 51% reported that they had utilized other healthcare than PHC during the same period. In a study by Saitz et al [ 42 ], which assessed factors associated with PHC, 41% of almost 6,000 people in addiction treatment reported that they did not have a PHC physician.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, side effects from opioids suggest that patients in OST might have a high prevalence of constipation, sleeping apnea and sexual dysfunction/hypogonadism. Previous research from Scandinavia and North America has also shown that patients in OST have poor self-rated health and a heavy burden of physical symptoms [19][20][21]. Medved et al [20] showed that almost three-quarters of Norwegian OST patients reported at least one chronic somatic condition, with hepatitis C (53%) and asthma (21%) being the most frequently reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation